Pertumbuhan Dan Produktivitas Cabai Rawit (Capsicum frutescens L.) Dengan Aplikasi Mulsa dan Pupuk NPK Mutiara - Nurhidayah Nurhidayah; Ramlan Ramlan; Anthon Monde (Universitas Tadulako, 2018)
This research starting in August to November 2014, which is located in the Porame village,Kinovaro District, Sigi Regency, Central Sulawesi province to the altitude of 235 meters above sea level. The Experimental method used was randomized block design in factorial with three replications. The first factor consisted of M0=unmulched, M1=black-silvered plastic mulch, M2=sawdust mulch and M3=rice straw-mulch, whereas the second factor were four NPK Mutiara dosages; P1=NPK dose 100 kg.ha-1 ,P2=NPK dose 200 kg.ha-1, and NPK dose 300 kg.ha-1. Each treatment was repeated 3 times so that overall there are 48 experimental units. The observed variables were the growth parameter root long ,plant height, tuber diameter, soil moisture content, weed dry weight, and yield (number and weight of chilli). The result showed that application of mulches give significant affect of all growth dan yield parameter, and NPK Mutiara fertilizer dosages were significant effect to root long, plant height , number of fruits per plant, fruit weight per plant, fruit weight per plot, fruit weight per hectare and soil moisture content. The best mulch and dose for chilli crops in upland area was black silvered plastic mulch whith NPK Mutiara fertilizer dose 300 kg/ha of 7.32 ton.ha-1